2022
DOI: 10.3389/fncel.2022.1061428
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the prognostic and immunological roles of aquaporin 4: A potential target for survival and immunotherapy in glioma patients

Abstract: Recent studies have revealed the critical role of AQP4 in the occurrence and development of gliomas. However, the role of AQP4 in immune regulation has not yet been reported. Many recent reports have identified the lymphatic system’s occurrence within the central nervous system (CNS) and the vital role of immune regulation in treating brain tumors. Therefore, the present study aimed to explore the role of AQP4 in the immune regulation of glioma. We used bioinformatics analysis to investigate the immunoregulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Reduced AQPs expression has been reported under pathological conditions ( Markou et al, 2022 ), including brain edema after stroke or trauma ( Papadopoulos et al, 2002 ; Clément et al, 2020 ; Dadgostar et al, 2022 ), neurological diseases ( Yang et al, 2011 ; Alvestad et al, 2013 ; Li et al, 2022 ), cancer progression and metastasis ( Lan et al, 2022 ), and inflammation. Of note, AQP1 and AQP4 are reported to be downregulated in the choroid plexus and the ependyma, respectively, of spontaneously hypertensive rat, as a putative compensatory mechanism to reduce the cerebrospinal fluid (CSF) production and volume ( Carnero Contentti and Correale, 2021 ; González-Marrero et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced AQPs expression has been reported under pathological conditions ( Markou et al, 2022 ), including brain edema after stroke or trauma ( Papadopoulos et al, 2002 ; Clément et al, 2020 ; Dadgostar et al, 2022 ), neurological diseases ( Yang et al, 2011 ; Alvestad et al, 2013 ; Li et al, 2022 ), cancer progression and metastasis ( Lan et al, 2022 ), and inflammation. Of note, AQP1 and AQP4 are reported to be downregulated in the choroid plexus and the ependyma, respectively, of spontaneously hypertensive rat, as a putative compensatory mechanism to reduce the cerebrospinal fluid (CSF) production and volume ( Carnero Contentti and Correale, 2021 ; González-Marrero et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a separate study identified a strong association between AQP4 expression and the expressions of epidermal growth factor receptor (EGFR), 4-aminobutyrate aminotransferase (ABAT), and platelet-derived growth factor receptor alpha (PDGFRA) in the classification of GBM. These factors have been proposed as potential targets for AQP4-related immunotherapy strategies [ 164 ]. Tan et al documented a negative correlation between the apparent diffusion coefficient and the expression of Aquaporin 4 (AQP4) mRNA in AS [ 165 ].…”
Section: The Importance Of Cell Crosstalk In Gliomasmentioning
confidence: 99%
“…Moreover, it has been shown to improve cerebral edema in animal studies [101,102]. While these findings are encouraging, more comprehensive studies evaluating their effect on peritumoral edema are urgently needed to establish their potential as therapeutic agents for peritumoral edema [103].…”
Section: Aquaporin Inhibitorsmentioning
confidence: 99%